0.2 V 8T SRAM With PVT-Aware Bitline Sensing and Column-Based Data Randomization - Do, Anh Tuan (2016)
In sub/near-threshold operation, SRAMs suffer from considerable bitline swing degradation when the data pattern of a column is skewed to ‘1’ or ‘0’. The worst scenarios regarding this problem occur when the currently read SRAM cell has different data compared to the rest of the cells in the same column. In this work, we overcome this challenge by using a column-based randomization engine (CBRE). This CBRE circuit randomizes data stored to SRAM. This makes distribution of “1” and “0” in each column close to 50%, significantly increasing bitline swing. To further improve the bitline swing, we employ bitline boost biasing and dynamic bitline keeper schemes. Based on the mentioned techniques, we fabricated a 256 rows×128 columns (32Kb) 8T SRAM array in 65 nm CMOS technology. In our silicon measurement, the SRAM array shows successful 200 mV operation at room temperature, where energy consumption and access time are 1 pJ and 2.5 s, respectively.